Organizational and Economic Mechanisms of Energy Security Ensuring of National Economy - Мазур І. M. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Organizational and economic mechanism of ensuring energy security of the national economy represented, was defined the essential systematic conception: a) content; b) principles; c) functions; d) stages of formation and implementation; e) implementation scenarios and development.